Training of animators within the specialty 242 “Tourism and recreation” - Shchuka Halyna; Kazakov Volodymyr; Hryniuk Diana (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського, 2024)
The article reveals the expediency and possibility of training specialists in tourism and recreation to perform animation activities. The relevance of the study is explained by the contradiction between the growth of consumer expectations concerning leisure services and the relatively low level of animation in the domestic tourist market. The purpose of the study is to determine the main aspects that ensure the effectiveness of preparation of the student of higher education for the organization of animation activities in tourism and recreation. The research was carried out using such methods as analysis of scientific literature, grouping and systematization of scientists’ points of view, comparison, synthesis and induction, modeling and generalization. The analysis of the legal support of the training process of future animators made it possible to state that the profession with such a name is not in the National Classifier of Professions, accordingly, there are no qualification characteristics for it. It has been proven that the requirements for an animator include the presence of knowledge and skills in various fields of activity (tourism, recreation, cultural studies, art, ethnography, pedagogy, psychology, etc.) and the formation of a number of personal character traits, among which the most important are artistry, sociability, stress resistance, creativity, ability to work in a team and persistence. It has been established that future animators are trained in several specialties that belong to different fields of knowledge. It has been determined that the ability to develop an animated tourist product is formed in the specialty "Tourism and recreation", to organize the leisure time of the population - in "Management of sociocultural activities" and "Culture studies". It is recommended that the training of hotel animators should be carried out at the disciplines of free choice of students, which will allow to involve only those students who have the desire and ability for this activity. When teaching the discipline, attention should be paid to the study of the specifics of providing animation services to different categories of consumers, the development and implementation of animation programs of various types.